Full tendon medial transposition of lateral rectus with augmentation sutures in cases of complete third nerve palsy. Issue 6 (22nd March 2018) - Saxena, Rohit; Sharma, Medha; Singh, Digvijay; Sharma, Pradeep
Abstract : Management options in third nerve palsy are limited as four of the six extraocular muscles are involved. Surgery has to be tailored on a case-to-case basis. Aim of this retrospective case series is to report 1-year outcomes of a modified surgical technique entailing full tendon transposition of lateral rectus to medial rectus augmented with posterior fixation sutures in four patients with complete third nerve palsy. All four cases showed significant improvement of vertical and horizontal deviation with long-term stability of correction. Choice of route of full tendon augmented transposition of lateral rectus to medial rectus can aid in achieving good correction of the vertical misalignment in addition to horizontal correction.